The Altered Expression of microRNA408 Influences the Arabidopsis Response to Iron Deficiency - Carrió-Seguí, Àngela; Ruiz-Rivero, Omar; Villamayor-Belinchón, Laura; Puig, Sergi; Perea-García, Ana; Peñarrubia, Lola (Frontiers in Plant Science, 2019)
MicroRNAs contribute to the adaptation of plants to varying environmental conditions by affecting systemic mineral nutrient homeostasis. Copper and iron deficiencies antagonistically control the expression of Arabidopsis thaliana microRNA408 (miR408), which post-transcriptionally regulates laccase-like multicopper oxidase family members LAC3, LAC12 and LAC13. In this work, we used miR408 T-DNA insertion mutants (408-KO1 and 408-KO2) and a previously characterized transgenic line overexpressing miR408 (35S:408-14) to explore how miR408 influences copper- and iron-dependent metabolism. We observed that the altered expression of miR408 diminished plant performance and the activation of the iron-regulated genes under iron-deficient conditions. Consistently with the low expression of the miR408-target laccases, we showed that the vascular bundle lignification of the 35S:408-14 plants diminished. The decrease in the phenoloxidase and ferroxidase activities exhibited by wild-type plants under iron deficiency did not occur in the 408-KO1 plants, probably due to the higher expression of laccases. Finally, we observed that the hydrogen peroxide levels under iron starvation were altered in both the 408-KO1 and 35S:408-14 lines. Taken together, these results suggest that Arabidopsis plants with modified miR408 levels undergo multiple deregulations under iron-deficient conditions